A one-pot successive cyclization–alkylation strategy for the synthesis of 2, 3-disubstituted benzo[b]thiophenes. Issue 18 (16th April 2021) - Cunningham, Christopher; Cloyd, Matthew; Phillips, Aimee; Khan, Soha; Whalen, Katherine; Kesharwani, Tanay
Abstract : A successive one-pot iodocyclization alkylation strategy was developed to synthesize highly functionalized 3-iodobenzo[ b ]thiophenes derivatives. Abstract : In this study, a new environmentally benign iodine-mediated one-pot iodocyclization/alkylation strategy for the synthesis of benzo[ b ]thiophene derivatives starting from 2-alkynylthioanisoles was developed. The synthesis of a diverse population of 2, 3-disubstituted benzo[ b ]thiophenes was achieved in high yields by employing moderate reaction conditions using 1, 3-dicarbonyl substrates as the nucleophile and various substituted propargyl alcohols as both the cyclization precursor and the alkylating agent. This method resulted in the formation of a series of complex structures obtained in a single step. Additionally, a strategy was devised for the one pot iodocyclization/oxidation of propargyl alcohols into carbonyl functionalized benzo[ b ]thiophene structures. These green one-pot reaction processes were designed to reduce wastes and byproducts while generating a complex substitution pattern on the benzo[ b ]thiophene structure. The reported methodologies may be used to synthesize more functionalized benzo[ b ]thiophene structures that can be used in both biomedical and organic electronic applications.